Anal Incontinence Among First Time Mothers: What Happens in Pregnancy and the First Year After Delivery?. Issue 3 (September 2016) - Johannessen, H.H.; Wibe, A.; Stordahl, A.; Sandvik, L.; Mørkved, S.
Abstract : ( Acta Obstet Gynecol Scand . 2015;94(9):1005–1013) The fundamental physical processes responsible for anal incontinence are not entirely understood. At the group level, it is typical for first time mothers to experience this problem during late pregnancy and the first postpartum year, but it is not yet clear why this is the case. The authors of this study investigated changes in continence status among individual healthy primiparous women from late pregnancy to the first postpartum year. The authors also sought to determine factors that might be associated with persistent anal incontinence and new onset incontinence at 1 year postpartum.